Chronic intermittent ethanol exposure during adolescence produces sex- and age-dependent changes in anxiety and cognition without changes in microglia reactivity late in life - Matthews, Douglas B.; Scaletty, Samantha; Trapp, Sarah; Schreiber, Areonna; Rossmann, Gillian; Imhoff, Bailey; Petersilka, Quinn; Kastner, Abigail; Pauly, Jim; Nixon, Kimberly (Frontiers in Behavioral Neuroscience, 2023)
Binge-like ethanol exposure during adolescence has been shown to produce long lasting effects in animal models including anxiety-like behavior that can last into young adulthood and impairments in cognition that can last throughout most of the lifespan. However, little research has investigated if binge-like ethanol exposure during adolescence produces persistent anxiety-like behavior and concomitantly impairs cognition late in life. Furthermore, few studies have investigated such behavioral effects in both female and male rats over the lifespan. Finally, it is yet to be determined if binge-like ethanol exposure during adolescence alters microglia activation in relevant brain regions late in life. In the present study female and male adolescent rats were exposed to either 3.0 or 5.0 g/kg ethanol, or water control, in a chronic intermittent pattern before being tested in the elevated plus maze and open field task over the next ∼18 months. Animals were then trained in a spatial reference task via the Morris water maze before having their behavioral flexibility tested. Finally, brains were removed, sectioned and presumptive microglia activation determined using autoradiography for [3H]PK11195 binding. Males, but not females, displayed an anxiety-like phenotype initially following the chronic intermittent ethanol exposure paradigm which resolved in adulthood. Further, males but not females had altered spatial reference learning and impaired behavioral flexibility late in life. Conversely, [3H]PK11195 binding was significantly elevated in females compared to males late in life and the level of microglia activation interacted as a function of sex and brain regions, but there was no long-term outcome related to adolescent alcohol exposure. These data further confirm that binge-like ethanol exposure during adolescence produces alterations in behavior that can last throughout the lifespan. In addition, the data suggest that microglia activation late in life is not exacerbated by prior binge-like ethanol exposure during adolescence but the expression is sex- and brain region-dependent across the lifespan.